Journeys to Teaching Qualitative Research Methods Online - Roulston, Kathryn; deMarrais, Kathleen; Paulus, Trena M. (LEARNing Landscapes, 2018)
Teaching in online spaces requires new roles and competencies. Presented as autoethnographic narratives, three faculty members describe their journeys into online graduate instruction in qualitative research methods. Areas of growth included effective course design and planning and strategies for building community. Challenges included keeping up with the technology and finding adequate resources. These narratives provide potential issues for consideration by faculty new to online instruction.